Thermal radiation effect on MHD stagnation point flow with partial slip - Praveen Kumar Dadheech; Navin Kumar; Priyanka Agrawal; Qasem Al-Mdallal (International Journal of Thermofluids)
The coupled effect of MHD stagnation point flow and thermal radiation over a shrinking sheet with partial slip is explored. The existence of dual solutions is investigated and studied for velocity, temperature and velocity gradient profiles. Then the transformed set of equations of the flow after applying suitable similarity solutions were encountered by Shooting Technique in conjunction with the fourth ordered Runge-Kutta method. Numerical solutions with graphical representation are studied. For more physical insight the skin friction coefficient number is also examined. In temperature profiles decreasing tendency is noticed with increased Prandtl number, thermal slip parameter values for both solutions. For the first solution, with increased velocity parameter and slip parameter, both the velocity profile and velocity gradient profiles increase and reverse pattern is noticed for the second solution. The current work has numerous practical applications in polymer technology, the manufacturing of glass fibers, and metallurgical processes such as annealing and tinning copper wires, as well as chilling continuous strips or filaments by pulling through quiescent fluids.